2022
DOI: 10.52808/bmsa.7e6.625.022
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de afrontamiento ante la crisis sanitaria: un estudio comparativo en enfermeros de costa y sierra ecuatoriana

Abstract: Se realizó una encuesta transversal de dos muestras separadas por conveniencia de enero a marzo de 2021 a fin de comparar la prevalencia de percepción de riesgo e identificar diferentes estrategias de afrontamiento en enfermeros de la costa y la sierra ecuatoriana. Las muestras incluyeron dos grupos de profesionales de enfermería para un total de 518. El 49,0% (n= 254) de los participantes laboraban en la sierra ecuatoriana y el 50,8% (n= 263) prestaban sus servicios en la costa ecuatoriana. Muestreados proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
2
3
2
Order By: Relevance
“…[ 2 , 5 , 6 , 7 , 9 , 11 , 22 , 23 , 26 , 58 , 60 ] contradict our findings, as they showed that the main sources of anxiety among health professionals were due to patient care, concern about becoming infected or infecting family members, work-related concerns, burnout, and fear of the unknown. Our results are inconsistent with [ 2 , 5 , 6 , 11 , 16 , 19 , 20 , 22 , 23 , 26 , 36 ], that reflected that the COVID-19 pandemic has generated higher levels of anxiety among health workers, regarding factors such as having been in contact with the virus or fear at work. Moreover, our results are contrary to the studies by [ 18 , 60 ], as they showed that health professionals have had to develop their profession in a precarious environment, putting both their individual and collective health at risk, considerably increasing their patients’ death anxiety; the predictor variables of this anxiety are the absence of personal protective equipment and high levels of burnout, emotional exhaustion, and depersonalization.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…[ 2 , 5 , 6 , 7 , 9 , 11 , 22 , 23 , 26 , 58 , 60 ] contradict our findings, as they showed that the main sources of anxiety among health professionals were due to patient care, concern about becoming infected or infecting family members, work-related concerns, burnout, and fear of the unknown. Our results are inconsistent with [ 2 , 5 , 6 , 11 , 16 , 19 , 20 , 22 , 23 , 26 , 36 ], that reflected that the COVID-19 pandemic has generated higher levels of anxiety among health workers, regarding factors such as having been in contact with the virus or fear at work. Moreover, our results are contrary to the studies by [ 18 , 60 ], as they showed that health professionals have had to develop their profession in a precarious environment, putting both their individual and collective health at risk, considerably increasing their patients’ death anxiety; the predictor variables of this anxiety are the absence of personal protective equipment and high levels of burnout, emotional exhaustion, and depersonalization.…”
Section: Discussioncontrasting
confidence: 99%
“…This seems to indicate that health professionals tried to protect their psychological health, and therefore their levels of anxiety, in the face of such an unprecedented threat in our recent history. These results support other studies that revealed that positive mental health and social, emotional, and psychological well-being have a positive effect, confer resilience, reduce the negative consequences of unpleasant experiences, promote an adaptive response to uncertain situations, and reduce the risk of suicidal ideation [ 13 , 14 , 24 , 25 , 29 , 30 , 31 , 34 , 36 , 40 , 45 , 49 , 53 , 54 , 82 , 83 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations